Gel electrophoresis (Henry Stewart Talks, 2026)
Fundamentals of gel electrophoresis, DNA, RNA, and protein separation, Types of gels: agarose and polyacrylamide, Sample preparation and loading, Visualization and result interpretation, Applications: genotyping, PCR, protein analysis, Importance and limitations in research and diagnostics